Analisis Faktor-Faktor yang Mempengaruhi Harga dan Kualitas Produk terhadap Keputusan Pembelian Melalui Minat Beli sebagai Variabel Intervening di UMKM Kacang Kulit Cap AS - Ahmat Nor Rhokim; Ira Setiawati; Henry Casandra Gultom (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to analyze the influence of price and product quality on purchasing decisions with purchase intention as a mediation variable in UMKM of Kacang Kulit Cap AS in Blora Regency. The method used is quantitative with an associative approach and multiple linear regression analysis using SmartPLS software. The sample of this study consisted of 389 respondents who were selected using the simple random sampling technique. Research results show that price and product quality have a positive and significant effect on purchase intention, while product quality does not have a direct significant effect on purchasing decisions. Purchase intention is proven to play a role as a significant mediation variable between price and product quality with purchasing decisions. These findings show that competitive prices and good product quality can increase purchase intention and purchasing decisions, thus providing practical implications for UMKM to continue to improve their pricing strategies and product quality.